Loose Connections and Liberal Theology: Blurring the Boundaries in Two Church‐Based Communities of Spiritual Practice. Issue 4 (5th April 2016) - Edgell, Penny; Robey, Derek
Abstract : We used a mixed methods approach—including ethnographic fieldwork, interviews, and a survey—to study two innovative Christian contemplative worship services housed in a mainline Protestant congregation in a midwestern city. These services employed boundary‐blurring practices designed to attract the "de‐churched"—those who had been involved in a Christian congregation in the past but who had at some point disengaged from organized religion. Though attracting some formerly de‐churched participants, these services were far more successful in attracting several other constituencies united by their liberal theology and by a preference for loose connections. We argue that these worship services are best understood as thriving communities of sustained spiritual practice where contemplative rituals sacralize both theistic and extra‐theistic, Christian and non‐Christian, symbols and beliefs.